Estudo de Nanofitas de h-BN e Nanofolhas de SiC por primeiros princípios - Gonçalves, Juliana Aparecida (2020)
Two-dimensional materials (2D) have been the focus of several kinds of research in recent years. Among these materials, we can highlight the "graphene-like" materials, as Boron Nitride hexagonal (h-BN) and Silicon Carbide (SiC). Although these materials are structurally similar to graphene, their electronic, optical, and magnetic properties are different, leading to different technological applications such as high-temperature diodes, solar cells, and sensors. Therefore, a detailed analysis of the properties of these nanostructures is of great importance. In this work, we employ First-principles calculations based on Density Functional Theory (DFT) to study the stability and the optical and electronic properties of edge-reconstructed three-layered h-BN nanoribbons. Also, we investigate silicon carbide nanosheets fluorination. In the first case, lines of pentagonal and heptagonal rings connect the system composed of three layers of h-BN at the edges. These rings have homopolar bonds B-B and N-N, which determine the stability of the system. Nanoribbons that have fewer homopolar bonds are the most stable relative to the h-BN layer. This result suggests that this type of reconstruction may occur in systems composed of three layers of h-BN, and they are more stable than their carbon analogs. Electronic analyses reveal that homopolar bonds’ presence introduces states located in the bandgap of the semiconductor ribbons. Homopolar bonds also significantly influence optical properties, primarily when the light path is in the direction of defects. Later, we investigated the influence of fluorine on the optical and electronic properties of SiC nanosheets. We observed that the adsorption of F atoms on SiC nanosheets is more favorable on Si sites. The strain caused by the four-fold-coordinated Si atoms in the flat SiC determines the relative position of the adsorbed F atoms: occupying the nearest neighbor Si sites, for the case where the F is on opposite sides of the sheet, or apart from each other if they are on the same side of the sheet. Optical and electronic properties do not depend on F atoms’ adsorption side on the sheet but in their relative distance. When F atoms bind to near Si sites, the system has a p-type semiconductor character. On the other hand, when the F atoms occupy far Si sites, the flat SiC becomes metallic. Also, F atoms’ adsorption affects the optical properties of SiC nanosheets and induces an optical anisotropy in the system.